HUBUNGAN PEMBERIAN MAKANAN PENDAMPING ASI DINI DENGAN KEJADIAN DIARE PADA BAYI USIA 0-6 BULAN DI POSYANDU KELURAHAN’ NGAGLIK - Mufida Annisa Rahmawati; Novi Budi Ningrum (Jurnal Ilmu Kebidanan, 2021)
Infants aged 0-6 months can grow optimally by relying on breast milk for the first 6 months of life. But in fact, before the age of 6 months, many babies have been given complementary feeding (MP-ASI). The purpose of this study was to determine the relationship between early complementary feeding and the incidence of diarrhea in infants aged 0-6 months at Integrated Healthcare Center Ngaglik, Batu City. This study uses a quantitative method with a cross sectional approach. The location and time of the study was at Integrated Healthcare Center Ngaglik, Batu City from January 2021 to March 2020. The independent variable (X) was early breastfeeding and the dependent variable (Y) was the incidence of diarrhea in infants aged 0-6 months. The total population is 32 mothers who have babies aged 0-6 months with a sample of 32 respondents. The sampling method used a total sampling technique, which is a sampling technique when all members of the population are used as samples. The data obtained were then analyzed using a descriptive statistical approach. By using a simple linear regression model method. The t value of the variable giving early complementary feeding (X) is 29.435 > ttable 2.039, which means that there is a significant relationship between the provision of early complementary feeding (X) and the incidence of diarrhea in infants aged 0-6 months (Y). The calculated F value is 866,415 > from the F value of 0.05 (4.17) meaning that there is a significant relationship between the variable of early breastfeeding (X) and the incidence of diarrhea in infants aged 0-6 months (Y). The R-square value of 0.967 means that the relationship between early complementary feeding and the incidence of diarrhea in infants aged 0-6 months is 96.7%, while the other 3.3% is influenced by other factors not studied. Keywords : MP-ASI, Diarrhea.